(untitled) (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2023)
The development of humanity, between industrial and technological revolutions, has caused damage to the ecology of the planet. This situation has allowed the emergence of the concept of sustainable development as a social process shaped by values, models, social learning, human, cultural and environmental behaviours. The objective was to describe the notion of sustainable development involved in the university context from andragogic practices at the National Experimental University Simón Rodríguez. The research adopted the naturalistic interpretative paradigm and the ethnographic method, where participant observation, field diary and in-depth interview to five teachers of the institution were applied. The information obtained was processed based on categorization, saturation, triangulation and theorization. The conclusions indicate that the university recognizes in its andragógicas practices the important elements of regional and local development, for the search of human and sustainable development, through continuous processes for the formation of competences.